Imperfect Competition - Kiminori Matsuyama (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
This paper constructs a general equilibrium model of imperfect competition and international trade and investigates the international transmissions of country specific aggregate demand shocks, such as changes in taste and fiscal policies. The impacts of coordinated fiscal expansion and of transfer payments are also discussed. The model has some curios resemblance with earlier Keynesian models of open economies, notably of the Machlup-Metzler variety, which emphasize the role of foreign trade multipliers in income determination in interdependent national economies.
Keywords: 330